A review of guidelines to resuming elective orthopaedic surgeries amid COVID-19 pandemic: deriving a simple traffic light model - Attia, A. K. (2024)
The COVID-19 pandemic has affected most healthcare systems around the world. Routine care operations such as outpatient clinics and elective surgery remain badly hit. This situation cannot continue for long as it puts patients at a higher risk for complications due to delayed management. Hence, it is essential to resume routine, especially elective surgery. Regarding orthopaedic practice, various authors and organisations have come out with guidelines to resume elective surgeries. However, clear consensus and common strategies need be derived. With this motive, we conducted a review of the literature for guidelines to resume elective orthopaedic surgery amid COVID-19 pandemic and shortlisted scholarly publications and information from regional organisations. We have summarised the information and derived an organised algorithm considering the guidelines provided by various sources. In this extraordinary time, guidelines come in as a relief for every surgeon who is in a dilemma whether to resume electives or not. Putting safety first, these guidelines or suitable versions should be followed at all levels wherever possible to avoid the lack of trained manpower in the event of staff morbidity.